The Effect of Career Development, Organizational Culture and Leadership on Performance - Oetari Poernamasasi, Ida (Dinasti International Journal of Digital Business Management, 2023)
The Literature Review article The Effect of Career Development, Organizational Culture and Leadership on Employee Performance is an employee performance article that aims to build a research hypothesis of the influence between employee performance variables that will be used in further research on employee performance, within the scope of Human Resource Management science. The method of writing this Literature Review article is by the librar method of Employee Performance research, Employee Performance sourced from online media such as Google Scholar, Mendele Employee Performance and other academic online media. The results of this literature review article are: 1) Career development affects employee performance; 2) Organizational culture affects employee performance; and 3) Leadership affects employee performance.